Climate change in deserts : past, present and future - Williams, M. A. J. (2014)
"This book reconstructs climatic changes in deserts and their margins at a variety of scales in space and time. It draws upon evidence from land and sea, including desert dunes, wind-blown dust, river and lake sediments, glacial moraines, plant and animal fossils, isotope geochemistry, speleothems, soils, and prehistoric archaeology. The book summarises the Cenozoic evolution of the major deserts of the Americas, Eurasia, Africa and Australia and the causes of historic floods and droughts. The book then considers the causes and consequences of desertification and proposes four key conditions for achieving ecologically sustainable use of natural resources in arid and semi-arid areas. Climate Change in Deserts is an invaluable reference for researchers and advanced students interested in the climate and geomorphology of deserts: geographers, geologists, ecologists, archaeologists, soil scientists, hydrologists, climatologists and natural resource managers."--
Climate change in deserts : an introduction -- Present-day desert environments -- Cenozoic evolution of deserts -- Adaptations to life in deserts -- Evolution of desert research -- Dating desert landforms and sediments -- Stable isotope analysis and trace element geochemistry -- Desert dunes -- Desert dust -- Desert rivers -- Desert lakes -- The pluvial debate -- Desert glaciations -- Speleothems and tufas in arid areas -- Desert soils, paleosols and duricrusts -- Plant and animal fossils in deserts -- Prehistoric occupation of deserts -- African and Arabian deserts -- Asian deserts -- North American deserts -- South American deserts -- Australian deserts -- Historic floods and droughts -- Desertification : causes, consequences and solutions -- Current climatic trends and possible future changes -- Towards sustainable use of deserts.
Includes bibliographical references (pages 531-619) and index.
Keywords: Paleoclimatology; Arid regions climate; Climatic changes; Deserts -- History